The roles of natural organic matter in chemical and microbial reduction of ferric iron - Chen, Jie; Gu, Baohua; Royer, Richard A.; Burgos, William D. (The Science of the total environment, 2003)
Although natural organic matter (NOM) is known to be redox reactive, the roles and effectiveness of specific functional groups of NOM in metal reduction are still a subject of intense investigation. This study entails the investigation of the Fe(III) reduction kinetics and capacity by three fractionated NOM subcomponents in the presence or absence of the dissimilatory metal reducing bacterium Shewanella putrefaciens CN32. Results indicate that NOM was able to reduce Fe(III) abiotically; the reduction was pH-dependent and varied greatly with different fractions of NOM. The polyphenolic-rich NOM-PP fraction exhibited the highest reactivity and oxidation capacity at a low pH (<4) as compared with the carbohydrate-rich NOM-CH fraction and a soil humic acid (soil HA) in reducing Fe(III). However, at a pH>4, soil HA showed a relatively high oxidation capacity, probably resulting from its conformational and solubility changes with an increased solution pH. In the presence of S. putrefaciens CN32, all NOM fractions were found to enhance the microbial reduction of Fe(III) under anaerobic, circumneutral pH conditions. Soil HA was found to be particularly effective in mediating the bioreduction of Fe(III) as compared with the NOM-PP or NOM-CH fractions. NOM-CH was the least effective because it was depleted in both aromatic and polyphenolic organic contents. However, because both soil HA and NOM-PP contain relatively high amounts of aromatic and phenolic compounds, results may indicate that low-molecular-weight polyphenolic organics in NOM-PP were less effective in mediating the bioreduction of Fe(III) at circumneutral pH than the high-molecular-weight polycondensed, conjugated aromatics present in soil HA. These research findings may shed additional light in understanding of the roles and underlying mechanisms of NOM reactions with contaminant metals, radionuclides, and other toxic chemicals in the natural environment.